2011
DOI: 10.1084/jem.20100977
|View full text |Cite
|
Sign up to set email alerts
|

Fumarates improve psoriasis and multiple sclerosis by inducing type II dendritic cells

Abstract: Fumarates suppress Th1 responses by blocking IL-12 and IL-23 production by dendritic cells via distinct pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
353
2
12

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(393 citation statements)
references
References 59 publications
(134 reference statements)
20
353
2
12
Order By: Relevance
“…In this study, we have identified Langerin neg cDCs as the critical pathogenic DC population initiating psoriatic plaque formation in mice via production of IL-23. To this end, our data extend previous findings and provide a functional rational to interfere with IL-23 activity or production using, for example, Ustekinumab, Fumarate, or Apilimod (37)(38)(39). Moreover, our work suggests that future strategies specifically blocking IL-23 secretion by Langerin neg cDCs may provide an effective treatment for psoriasis avoiding the problems associated with the general immunosuppression seen in many therapeutic approaches today.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, we have identified Langerin neg cDCs as the critical pathogenic DC population initiating psoriatic plaque formation in mice via production of IL-23. To this end, our data extend previous findings and provide a functional rational to interfere with IL-23 activity or production using, for example, Ustekinumab, Fumarate, or Apilimod (37)(38)(39). Moreover, our work suggests that future strategies specifically blocking IL-23 secretion by Langerin neg cDCs may provide an effective treatment for psoriasis avoiding the problems associated with the general immunosuppression seen in many therapeutic approaches today.…”
Section: Discussionsupporting
confidence: 83%
“…14 In addition, DMF switched the immune system towards a Th2 anti-inflammatory type response through the activation of type II DCs and the suppression of type I DCs, which consequently inhibits the generation of inflammatory Th1 or Th17 cells. 17 It has been reported that DMF inhibits the proliferation of melanoma cells 18 and synergizes with dacarbazine to influence the migration of tumor cells. 25 Whether DMF or the DMF derivative MMF exerts any effect on NK cells remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, DMF inhibits dendritic cell (DC) maturation through a reduction in the release of the inflammatory cytokines IL-6 and IL-12. 16 Ghoreschi et al 17 observed that fumarates switch the immune system towards a Th2 type response. In addition, DMF suppresses STAT1 phosphorylation in DCs, arrests the production of type I DCs and induces the production of type II DCs, which favors the activation of Th2 cells and inhibits the expression of T-bet (Th1 cells) or RORct (Th17 cells).…”
Section: Introductionmentioning
confidence: 99%
“…Reports showed that IL-23 production by DC is inhibited by IL-4 and that downmodulation of DC and IL-23p19 is an early effect during psoriasis treatment (20,26). We did not observe a reduction in IL-23p19 mRNA expression in epidermal and whole PP skin after IL-4 stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In psoriatic epidermal cells, the expression of the IL-4 receptor is increased (19). Fumarate treatment induces IL-4-producing Th2 cells in vivo and generates type II DC that produce IL-10 instead of IL-12 and IL-23 (20). Clinical improvement of psoriasis is accompanied by activation of IL-4 signaling pathways including upregulated expression of GATA3 (21).…”
mentioning
confidence: 99%